Setting the agenda for American archaeology : (University of Alabama Press, 2001)
In the 1920s and 1930s, the fascination that Americans had for the continent's prehistoric past was leading to a widespread and general destruction of archaeological evidence. In a drive toward the commercialization of antiquities, amateur collectors and "pot hunters" pillaged premier and lesser-known sites before the archaeological record could be properly investigated and documented. Adding to the problem was a dearth of professionals and scholars in the field to conduct professional investigations and to educate the public about the need for preservation and scientific research methods. In stepped the National Research Council, a division of the National Academy of Sciences, the Committee on State Archaeological Surveys. The CSAS initiated an enormously successful outreach program to enlist the aid of everyday citizens in preserving the fragile but valuable prehistoric past. Meetings held in St. Louis, Birmingham, and Indianapolis provided nuts-and-bolts demonstrations by trained archaeologists and laid out research agendas that both professionals and amateurs could follow. Setting the Agenda contains the complete reports of the three NRC conferences, a short publication on the methods and techniques for conducting archaeological surveys, and a guide for amateur archaeologists. An extensive introduction by the editors sets these documents in context and provides insight into the intentions of the NRC committee members as they guided the development of American archaeology.